Students' Attitude in Reading Classroom - Ayu Windyawati Puspita Wardani; Dina Merris Maya Sari (Peneliti.net, 2020)
This study focuses on the attitude of students of class 2019A STKIP PGRI Sidoarjo EnglishEducation Study Program in reading classroom. The purposes of the study were to find outthe ability of student’sclass 2019A STKIP PGRI Sidoarjo English Education Study Programand the attitude of student’s class 2019A STKIP PGRI Sidoarjo English Education StudyProgram. The method applied was quantitative, where the questioners and scoring rubicwere used as the instrument data collection methods. The questioners cons isted of 15 yes -no questions in a student’s response to ability and attitude in reading classroom with GoggleForm . The result of the test showed that the majority of the students of class 2019A STKIPPGRI Sidoarjo English Education Study Program 74.8% show the positive response towardreading class, and only 25.2% get a negative response. Then got data based on scoring rubicwas carried out by assessing and correcting the reading final exam results of nine studentsof class 2019A. The result findings presentation of respondent data based on readingcomprehension according to Brown (2003:215).